Biomechanical Characteristics of Human Motors (Global Scientific Review, 2024)
The work provides detailed information about changes in the morphological characteristics of a person's stature, motility and morphofunctional indicators, biomechanical parameters of natural locomotion during ontogenesis. Studied the sickle structure of dynamogram types and types of natural human locomotion